The Effect of Organizational Compliance on High Performance: An Analytical Research in the General Company of Leather Industries / Cotton Factor - Faisal Younis, Anfal; Mohammed Ali, Shiffaa (Journal of Economics and Administrative Sciences, 2023)
This research aims to identify how organizational compatibility, which represents the independent variable, affects higher performance, which is considered a dependent variable, given the importance of these variables in industrial organizations and their clear impact on their stability, survival, and growth in the light of changing environmental challenges.  Where the practical research problem was represented by the weakness of awareness of the importance toward organizational compatibility and its dimensions (organizational loyalty, organizational similarity, affiliation or membership, compatibility with goals, and compatibility with values), which is meant by the individual's compatibility with the organization in which he/she works within, and its impact on high performance with its dimensions (self-directed work teams,  effective recruitment, in-depth training, quality of workers, and employee motivation: rewards and incentives). To achieve the research objective, several main and sub-hypotheses have been suggested. Therefore, the research seeks to bring the attention of the leaders’ company toward the importance of research variables. The analytical (descriptive) approach was relied as a research design. The questionnaire served as the fundamental tool employed by the researchers for data collection and it included 52 questions, as the questionnaire was filled out by a sample of workers in the General Company for Textile and Leather Industries / Cotton Factory, with a total of 130 individuals( male and female), the most important research results are the existence of a correlation and impact of organizational compliance on high performance with its five dimensions.